Metastasis‐specific patterns of response and progression with anti‐PD‐1 treatment in metastatic melanoma. (7th December 2017) - Lee, Jenny H. J.; Lyle, Megan; Menzies, Alexander M.; Chan, Matthew M. K.; Lo, Serigne; Clements, Arthur; Carlino, Matteo S.; Kefford, Richard F.; Long, Georgina V.
Summary: This study evaluated patterns of response as discerned by comprehensive metastasis‐specific analysis in metastatic melanoma patients receiving anti‐PD‐1 antibodies. Bi‐dimensional measurements of every metastasis in patients enrolled in the KEYNOTE‐001 trial at a single institution were obtained at baseline and throughout treatment. Twenty‐seven evaluable patients had 399 baseline metastases measurable on CT imaging. Complete response (CR) which occurred in 52.6% of metastases was smaller (mean 223 mm 2 versus 760 mm 2, p  < .01) and occurred more frequently in the lungs (65% versus 39.4%, p  < .01). Response was heterogenous (new/progressing metastases alongside CR metastases) at first assessment in 4/14 patients with objective response (OR) as opposed to 7/13 patients with non‐OR. CR of individual metastases is common and influenced by site and size. Most patients with OR demonstrate homogenous regression in all metastases at the first assessment. In contrast, patients with early heterogeneity had a poor outcome.